Economic valuation and its determinates of improve solid waste management services: A study of double-bounded contingent valuation in Gondar City Ethiopia - Kassahun Tassie; Anteneh Mulugeta; Yenesew Sewunet; Getenet Asifaw (Sustainable Environment)
One of the byproducts of life is waste. Volume and complexity of solid waste have increased due to urbanization, economic growth, and rising living standards in cities. In most Ethiopian cities, residents do not pay for municipal solid waste management services. The study aims to examine Economic valuation and its’ determinates of improve solid waste management services in Gondar, Ethiopia. The study was conducted through face-to-face interviews with 222 randomly selected households. According to the survey results, 192 (87.3%) of the sampled households were willing to pay for better solid waste management services, with a mean willingness to pay of 34.48 and 17.0756 Ethiopian Birr (ETB) per month per household from the double-bounded dichotomous and open-ended contingent valuation methods, respectively. The total willingness to pay from open-ended and double-bounded contingent valuation methods is 941,361 and 1,900,848 ETB, respectively. Furthermore, the outcomes from the bivariate probit model indicated a positive and significant correlation between the willingness to pay bid amounts and both education and income. The study reveals that households’ inclination to contribute to enhanced solid waste management services is significantly and inversely affected by factors such as age, marital status, as well as the levels of Bid1 and Bid2. When allocating service charges, the city municipality should consider the amount of solid waste generated and the income level of the households. Awareness creation is important for better solid waste management. Additionally, the city municipality encouraged to facilitate awareness among urban households to minimize illegal waste disposal and encourage their participation.